Strategi Adaptasi Masyarakat Samudera Pasai Menghadapi Luapan Sungai Pasai - Repelita Wahyu Oetomo (Balai Arkeologi Sumatera Utara, 2008)
AbstractThe Pasai peoples depend on Pasai River very much. Much activities around the Pasai .river caused superficiality of it. People had to adapt to the condition that’s always flooding.